Épiphanies noires - Nissim, Liana (Ponti/Ponts, 2021)
This essay is the result of the study of two works, the catalog of the exhibition Le Modèle noir de Géricault à Matisse (Musée d’Orsay, 26 March-21 July 2019) and the book L’Africa esposta. Realtà e rappresentazioni del continente africano nelle esposizioni universali dall’Ottocento al 2015, published in 2018 by the research group of the University of Milan, “Le ricchezze dell’Africa”. We examine the complex historical problems that have characterized the cultural and artistic relations between the Blacks of different origins present in France in the nineteenth century and in the first half of the twentieth, relations marked by trafficking, slavery and its abolition, colonialism. It can be seen that over time (despite the different, and sometimes opposing, orientations of some artists), the undisputed perception of the superiority of the white race over all the others, and especially over the black race, has been consolidated in the European mentality, a perception strongly favored by the so-called “scientific racism” first, by the interests of the colonial empires then. Proof of this are ethnic shows and human zoos, deplorable phenomena of brutal racism, signs of a historical reality on which, even today, it is necessary to reflect to break the filters that hinder (still!) our looks and our vision of man and the world.